Factors that contribute to the student`s choice to study at Multimedia College (MMC) rather than other private colleges in Alamesra Kota Kinabalu Sabah / Anati Awang Bair - Awang Bair, Anati (2014)
The purpose of this particular research which is a study on the factors that contribute to the students choice to study at Multimedia College (MMC) rather than other private colleges in Alamesra, Kota Kinabalu, Sabah. The purpose of this research is to identify the factors that contributed to the students selecting Multimedia College to further their studies. The objectives of this research are what are studying facilities and benefits that are available in MMC, to identify the factors that contributed to students election to study at MMC and also to make suggestions and recommendations for MMC in order to enhance their service and facilities better and improved. The finding from this research identified that the students choose to study at MMC because of the quality of the faculty followed by the job opportunity after graduate, fees and the course offering are also the factor of students choose to study at MMC. There are several recommendation from the respondents in order to improve the services and facilities at Multimedia College.